Metabolite Profiling of Feces and Serum in Hemodialysis Patients and the Effect of Medicinal Charcoal Tablets - Sixiu Liu; Shanshan Liang; Hua Liu; Lei Chen; Lingshuang Sun; Meng Wei; Hongli Jiang; Jing Wang (Karger Publishers, 2018)
Background/Aims: Recently, the colon has been recognized as an important source of various uremic toxins in patients with end stage renal disease. Medicinal charcoal tablets are an oral adsorbent that are widely used in patients with chronic kidney disease in China to remove creatinine and urea from the colon. A parallel fecal and serum metabolomics study was performed to determine comprehensive metabolic profiles of patients receiving hemodialysis (HD). The effects of medicinal charcoal tablets on the fecal and serum metabolomes of HD patients were also investigated. Methods: Ultra-performance liquid chromatography/mass spectrometry was used to investigate the fecal and serum metabolic profiles of 20 healthy controls and 31 HD patients before and after taking medicinal charcoal tablets for 3 months. Results: There were distinct metabolic variations between the HD patients and healthy controls both in the feces and serum according to multivariate data analysis. Metabolic disturbances of alanine, aspartate and glutamate metabolism, arginine and proline metabolism figured prominently in the serum. However, in the feces, alterations of tryptophan metabolism, lysine degradation and beta-alanine metabolism were pronounced, and the levels of several amino acids (leucine, phenylalanine, lysine, histidine, methionine, tyrosine, and tryptophan) were increased dramatically. Nineteen fecal metabolites and 21 serum metabolites were also identified as biomarkers that contributed to the metabolic differences. Additionally, medicinal charcoal treatment generally enabled the serum and fecal metabolomes of the HD patients to draw close to those of the control subjects, especially the serum metabolic profile. Conclusion: Parallel fecal and serum metabolomics uncovered the systematic metabolic variations of HD patients, especially disturbances in amino acid metabolism in the colon. Medicinal charcoal tablets had an impact on the serum and fecal metabolomes of HD patients, but their exact effects still need to be studied further.